Research in personnel and human resources management. Vol. 21 - Ferris, Gina.; Martocchio, Joseph J.; University of Illinois at Urbana-Champaign. (Bingley, U.K. : Emerald, 2002)
This series publishes monograph-length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 21 contains eight papers on critical issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field.
Overview / Gerald R. Ferris, Joseph J. Martocchio -- Personality research in the organizational sciences / Pamela L. Perrewé, Paul E. Spector -- Social influence processes in organizations and human resources systems / Gerald R. Ferris, Wayne A. Hochwarter, Ceasar Douglas, Fred R. Blass, Robert W. Kolodinsky, Darren C. Treadway -- Mentoring : what we know and where we might go / Raymond A. Noe, David B. Greenberger, Sheng Wang -- Hierarchical team decision making / Stephen E. Humphrey, John R. Hollenbeck, Christopher J. Meyer, Daniel R. Ilgen -- Information technology and human resources management : harnessing the power and potential of netcentricity / Kathryn M. Bartol, Wei Liu -- Knowledge management in global organizations : implications for international human resource management / Rabi S. Bhagat, David L. Ford, Coy A. Jones, Robert R. Taylor -- Cross-cultural differences in responses to feedback : implications for individual, group, and organizational effectiveness / Eugene F. Stone-Romero, Dianna L. Stone -- Strategies for detecting moderator variables : a review of conceptual and empirical issues / Eugene F. Stone-Romero, Dimitri Liakhovitski.
Print version record
Keywords: Business & Economics -- Human Resources & Personnel Management; Psychology -- Applied Psychology; Personnel & human resources management; Personnel management